VOLATILITAS NILAI TUKAR RUPIAH TERHADAP DOLLAR SELAMA 2 TAHUN PEMERINTAHAN JOKOWI-JK: APLIKASI MODEL ARIMA - Shahreza, Dhona (Economic Faculty, Attahiriyah Islamic University, 2017)
This article aims to analyze the movement of Rupiah to US Dollar rate and to create ARIMA forecasting model. daily Rupiah middle rate from M11 2014 to M06 2017 is taken from www.bi.go.id. Eviews 6 portable is implemented to analyze the data. The results show that the movement of Rupiah to US Dollar rate tends to fluctuate and ARIMA (1,0,0) model ã€–kursã€—_t=13395.21+0.983776ã€–kursã€—_(t-1) indicates that Rupiah rate affected by previous day(t-1) rate and model can be used to forecast the future exchange rate. Keywords: ARIMA model, forecasting